BeadArray-based genotyping. - Butler, H; Ragoussis, J (2008)
There is a demand for technologies that allow the interrogation of large numbers of SNP polymorphisms, both in whole-genome panels and in smaller custom designed sets, to attempt to elucidate the nature of complex disease through linkage and association studies. The Illumina BeadArray technology offers a flexible platform for such analyses through two assays: GoldenGate, as described in this chapter, and Infinium II. Both assays utilize the BeadArray technology, where targeted regions of DNA are immobilized on beads randomly arranged into arrays, and the SNPs visualized through fluorescent tags, which differentiate among alleles. The platform is scalable such that mid- to high-throughput projects can be designed and completed in either a manual or automated mode. Small amounts of starting material are required, and in the case of GoldenGate, some level of sample degradation can be tolerated. The assays are efficient and reliable giving high pass rates and concordance levels.